Strategi Penanggulangan Kekerasan terhadap Anak di Kota Denpasar - Siahaan, Marsaulina Sarah Yeareve; Wiasti, Ni Made; Suarsana, I Nyoman (Sunari Penjor : Journal of Anthropology; Vol 8 No 2 (2024): Volume 8. No. 2. September 2024DO - 10.24843/SP.2024.v8.i02.p06, 2024)
Incidents of violence against children in Bali Province can be found in all districts, including in Denpasar City. All of these phenomena certainly do not just happen, but involve the efforts of the family as the child's closest environment in preventing acts of violence against children through various strategies. Research to explore the strategies used by families in Denpasar City in dealing with violence against children. This research uses a qualitative approach by collecting data through in-depth interviews with three informants who have experience in dealing with violence against children. The research results show that families use various strategies, such as good communication, appropriate punishment, the ability to regulate emotions, sexual education, meeting children's needs, and awareness of family responsibilities. These strategies have positive impacts, such as children growing up to be confident, brave enough to express their opinions, and live in a safe and loving environment. This research provides a better understanding of efforts to overcome violence against children at the family level and the importance of creating a safe space for children and creating a harmonious family.